Validation of road traffic noise and prediction of traffic increases along a highway in Hungary using noise maps - Karam Waleed Katw; Bela Tóthmérész; Denes Kocsis (Environmental Monitoring and Assessment, 2026)
In urban regions of Europe, road traffic noise ranks as the second most significant environmental stressor, following air pollution. This study measures urban road traffic noise using a noise map that is validated by in situ noise measurements, and it predicts a future scenario for increased traffic in 2030 by altering the traffic composition and overall vehicle count whilst evaluating the noise exposure at building façade points. The investigation used the noise mapping software IMMI and employed the CNOSSOS-EU method to assess road traffic noise. There are strong connections between the actual noise measurements and the model results, with an average difference of 1.09 dB(A) on the roadside, whilst on the receptor side it was 0.81 dB(A). Urban transport development provides the basic data to predict the noise levels affecting the designated area. Based on the 35% increase expected in average day and night traffic flow in 2030, the results indicate an additional 307.14% of people will be exposed to noise levels between 55 and 60 dB(A) throughout the day (L day ), and an additional 450.00% of people will be exposed to noise levels between 50 and 55 dB(A) at night (L night ). By 2030, the continual increase in urban traffic, driven by population growth, will result in significantly heightened noise levels in densely populated areas. Furthermore, average day and night noise levels in high-traffic zones are anticipated to exceed 55 dB(A) without strategic urban planning and stringent enforcement of noise laws, which would exceed WHO health safety standards.

Suspended sediment concentration recognition method based on MobileViT-CBAM - Jie Liu; Jin Jin; Qingquan Fu; Zhanpeng Pan; Zhanli Ma; Xiaoyang Li; Hui Yong (Environmental Monitoring and Assessment, 2026)

Comparative retention of polypropylene and polyvinyl chloride microplastics in sand, clay, and silt loam soils under a single-concentration batch condition - Sasivimon Aimampiy; Aophat Choonut; Tsuyoshi Imai; Alissara Reungsang; Sureewan Sittijunda (Environmental Monitoring and Assessment, 2026)

Polycyclic aromatic hydrocarbons, toxic and potentially toxic elements in Pelophylax esculentus complex embryos from the UNESCO-Protected Drava River Floodplain (Croatia) - Dora Bjedov; Brankica Kartalović; Mirna Velki; Kristina Habschied; Nataša Turić; Alma Mikuška (Environmental Monitoring and Assessment, 2026)

Evaluation of nuclear abnormalities in buccal mucosa cells of grazing cattle from pastures routinely treated with 2,4-D: an exploratory field study - Cimara Sales Vieira; Rafael Carneiro Silva; Juliana Ferreira da Silva; Iasmim Adelardo Queiroz; Andreia dos Santos Moraes; Damiana Mírian da Cruz e Cunha; Aparecido Divino da Cruz; Alex Silva da Cruz (Environmental Monitoring and Assessment, 2026)
The herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) is widely used in agricultural systems, raising concerns about its potential genotoxic effects on non-target organisms. This cross-sectional observational field study evaluated nuclear abnormalities in exfoliated buccal mucosa cells from 36 grazing cattle maintained on a farm where 2,4-D was routinely used in Goiás, Brazil, and investigated their relationship with physiological variables, including rectal temperature, body weight, and body condition score (BCS). A total of 1,000 cells per animal (36,000 cells) were analyzed to quantify micronuclei and other nuclear abnormalities. Statistical analyses included the Shapiro–Wilk test, Mann–Whitney test, rank-biserial correlation, Spearman correlation, Benjamini–Hochberg correction for multiple comparisons, and multivariable Poisson regression with robust standard errors. Overall, low frequencies of micronuclei and other nuclear abnormalities were observed. Although nominal associations were identified in the unadjusted analyses, none remained statistically significant after Benjamini–Hochberg correction for multiple comparisons. In the multivariable Poisson regression model, body condition score remained inversely associated with micronucleus frequency (incidence rate ratio = 0.274; 95% confidence interval: 0.128–0.587; p =

Impact of allometric reference selection on management scale aboveground biomass estimation via Sentinel-2 and machine learning - Ahmet Salih Değermenci; İrfan Öztürk; Mehmet Küçük (Environmental Monitoring and Assessment, 2026)

eDNA-based assessment of microbial dynamics in response to persistent contaminants and degraded water quality in a hypereutrophic urban reservoir - Juliana S. M. Pimentel; Maria Clara V. M. Starling; Camila C. Amorim; Valquíria F. L. Viana; Alessandra S. Martins; Daniel A. S. Rodrigues; Luciana P. M. Brandão; Nadieh de Jonge; Niels O. G. Jørgensen; Louise Schlüter; Matt Simcik; Jeppe Lund Nielsen (Environmental Monitoring and Assessment, 2026)
Urban freshwater ecosystems are increasingly exposed to mixtures of pollutants, including per- and polyfluoroalkyl substances (PFAS). However, their ecological effects remain poorly understood, especially in tropical regions with limited sanitation infrastructure. This study investigated PFAS contamination, water quality, and microbial community structure in Pampulha Lake, a tropical urban reservoir in southeastern Brazil. Spatiotemporal patterns in prokaryotic and eukaryotic diversity were assessed over a year (2022–2023) using environmental DNA metabarcoding of 16S and 18S rRNA genes by integrating taxonomic data with PFAS concentrations and water quality. Physicochemical and multivariate analyses revealed strong seasonal and spatial heterogeneity, influenced by eutrophication, hydrological variability, and pollution gradients. Among the seven PFAS detected above quantification limits, PFBS and PFOA were the most common. Prokaryotic communities showed significant correlations with PFAS, especially with sulfonated forms, while eukaryotic communities were more stable. Diversity patterns highlighted microbial community sensitivity to environmental stress. Overall, results indicate that PFAS influenced microbial assemblages, supporting their inclusion in monitoring frameworks, and eDNA was proved effective for assessing ecological risks in tropical urban reservoirs.

Urban forests as carbon reservoirs: comparative assessment across Delhi-NCR - Archana Rani; Aishwarya Rajlaxmi; Prerna Singh; Manoj Kumar (Environmental Monitoring and Assessment, 2026)

A scale-optimized assessment of the spatiotemporal evolution of rice–crayfish field fragmentation in the Jianghan Plain, China - Lei Shi; Yun Bao; Xu He; Weiyang Ma; Lei Yu (Environmental Monitoring and Assessment, 2026)

Seasonal responses of land surface temperature to landscape patterns and multi-objective optimization in urban–rural fringe: a case study of Changqing District of Jinan City, China - Min Wang; Zihan Li; Xiaoyu Wang; Zhongjian Shen; Jinyan Wang; Huanan Wan; Chang’an Zuo; Tianran Wang (Environmental Monitoring and Assessment, 2026)

Quantifying the spatial relationship between urban land use and carbon emissions using remote sensing and GIS - Hatice Oya Eşbah; Anil Akin (Environmental Monitoring and Assessment, 2026)

Restoration interventions enhance plant species diversity and composition in the humid tropical highlands of Ethiopia - Annissa Muhammed; Eyasu Elias; Weldemariam Seifu; Abreham Berta; Abrham Seyoum (Environmental Monitoring and Assessment, 2026)

An AHP-based multicriteria screening framework for preventive pesticide monitoring in data-limited tropical rice catchments - Lina María Cerón-Arámburo; Liliana Carolina Luis-Rincón (Environmental Monitoring and Assessment, 2026)

The determinants of forest area in Brazil: U-shaped association for gross domestic product per capita and for the value of agricultural production per hectare - Slim Ben Youssef (Environmental Monitoring and Assessment, 2026)

Lead and other elements in the diet of children (aged 0–7 years) across 20 Chinese provinces at a home-level survey: seasonal variations of element levels and risks in food, urine, and feces in healthy individuals - Maoyuan He; Xiaoping Li; Yu Gao; Pengyuan Jin; Zebo Yang; Jiayi Li; Xuelian Kui; Tunyang Geng; Xueming Zheng; Xu Zhang; Xiangyang Yan (Environmental Monitoring and Assessment, 2026)

Assessment of natural radioactivity with radiological hazards and spatial distribution of radionuclides in soils, sediments from coastal and non-coastal regions of southeastern Bangladesh - Md. Abadat Hossain; AKM Saiful Islam Bhuian; Mohammad Belal Hossen (Environmental Monitoring and Assessment, 2026)

Electrochemical biosensors for saxitoxin detection: advances, limitations, and challenges for market transition - Isadora Bernardes Sequalini; Thiago Teixeira da Silva; Larissa Victoria do Carmo de Oliveira; Nirton Cristi Silva Vieira (Environmental Monitoring and Assessment, 2026)
Saxitoxins, produced by freshwater cyanobacteria and marine dinoflagellates, block neuronal sodium channels and can cause paralysis or death. They contaminate drinking water, bioaccumulate in aquatic organisms, and pose serious health risks. Conventional detection methods, though reliable, are costly, time-consuming, and require specialized personnel, limiting rapid or on-site use. Biosensors have emerged as attractive alternatives, with electrochemical platforms standing out for their high sensitivity, low cost, miniaturization potential, and easy integration into portable devices. These advantages make them promising tools for in situ monitoring of saxitoxins and justify a dedicated review. This work critically analyzes electrochemical biosensors for STX detection, highlighting advances, limitations, and challenges toward commercialization. We discuss operating principles, recognition elements, analytical performance, and classify devices by electrochemical technique (potentiometric, impedimetric, voltammetric), providing a comparative perspective on their respective strengths and limitations. Despite remarkable sensitivity—often below regulatory limits—key obstacles remain: lack of fabrication standardization, poor long-term stability, limited validation with naturally contaminated samples, insufficient robustness for complex matrices, low reproducibility, and absence of regulatory approval pathways. In addition, challenges associated with fabrication scalability and interlaboratory reproducibility continue to hinder the transition from proof-of-concept devices to commercially viable technologies. Overcoming these barriers is crucial for translating laboratory prototypes into reliable, field-deployable devices for environmental monitoring and food safety applications. Future developments should focus on improving robustness, reproducibility, and analytical validation to accelerate the practical implementation of electrochemical STX biosensors.

Changes in groundwater storage in the southern plain of Western Nepal: insights from remote sensing, modeling, and field studies - Prajwol Aryal; Vishnu Prasad Pandey; Bhesh Raj Thapa; Nabin Tiwari (Environmental Monitoring and Assessment, 2026)

Productivity-based sampling for field-scale soil organic carbon mapping: from regional models to carbon farming needs - Milutin Pejović; Milan Kilibarda; Dragutin Protić; Branislav Bajat (Environmental Monitoring and Assessment, 2026)

A machine learning approach to predict river hydrographs for water quality sampling - Eloise Wilson; Melanie Shaw; Frederick Bennett; Zoe Bainbridge; Stephen Wallace; Ryan Turner (Environmental Monitoring and Assessment, 2026)
Hydrology and water quality are innately linked, as flow dynamics control the transport of pollutants within river systems. Consequently, the timing of sample collection in water quality monitoring programs strongly influences the accuracy of estimated pollutant loads. To minimise error, concentrations should be sampled across the hydrograph, capturing the rising limb, peak, and falling limb, to reflect the dynamic nature of pollutant transport. However, in river systems with variable flow regimes, predicting the timing and duration of events is challenging. Monitoring programs often resort to oversampling to ensure that critical periods are represented, but this approach increases effort and cost. In this study, we apply probabilistic gradient boosting decision tree regression (CatBoost) to forecast river height in a tropical, fast-response catchment characterised by high-flow variability, using hourly rainfall, discharge, and river height data collected over a 15-year period. Model performance was evaluated across forecast horizons ranging from 1 to 48 h. The models reproduced hydrograph magnitude, shape, and timing with high accuracy at short horizons (1–12 h), while forecast confidence and accuracy declined progressively at longer horizons (24–48 h). Forecast performance also varied across flow regimes: low flows were predicted accurately across all horizons, moderate flows reliably up to the 24-h horizon, and high flows up to the 12-h horizon. Predictive skill declined for extreme events; however, forecasts remained operationally valuable up to the 12-h horizon. These findings highlight the potential for short-term forecasts to support adaptive, resource-efficient sampling programs and reduce reliance on oversampling while maintaining pollutant load accuracy.

Spatio-temporal analysis of coal mining impacts on land cover using remote sensing: a case study of Northern Coalfields, India - Sanyam Dadhich; Sandeep Kumar Asarapalli; Amrendra Kumar; A. Jamal; Suresh Sharma; Md. Muzzammil (Environmental Monitoring and Assessment, 2026)

Mesoscale eddy dynamics and their influence on biological productivity in the western Bay of Bengal during the fall intermonsoon - Vimal Kumar K.G.; Sajeev R; Smitha B.R; Jayalakshmi K.J.; J. K. Lix; S. Akash; Rasheed K; Sanjeevan V.N. (Environmental Monitoring and Assessment, 2026)

Hybrid ensemble machine learning algorithms for landscape ecological vulnerability assessment to riverbank erosion - Vicky Anand; Vishnu D. Rajput; Aastha Sharma; Amrita Bajaj; Shekh Moinuddin; Saglara S. Mandzhieva; Tatiana Minkina; Denis Krivoguz (Environmental Monitoring and Assessment, 2026)

Hydrological response of a multi-aquifer groundwater system to long-term clustered mine drainage - Yue Ding; Deqiang Wang; Kangyouran Zhou; Yunhua He; Sheng Yang; Chao Jia; Xiao Yang (Environmental Monitoring and Assessment, 2026)

Divergent trends in near-surface ozone and nitrogen dioxide and ozone-attributable health burden in the Huaihe River Basin, China, 2013–2024 - Minxia Liu; Siqian Wang; Yi Yang (Environmental Monitoring and Assessment, 2026)

Primary inventory of phytoplankton as ecological bioindicators in the Lobe Estuary, Kribi (Southern Cameroon) - Steeve Arnold Fotue Simo; Pierre Paul Semengue; Ulrich Joel Félicien Bilounga; Huguette Christiane Emvoutou; Célestin Rodrigue Ebonji Seth (Environmental Monitoring and Assessment, 2026)

Refined analysis of microplastics in endemic fish species from Lake Victoria using µ-FTIR and pyrolysis GC-MS - Timothy Omara; Barbora Benetková; Ivan Sumerskii; Patrick Ssebugere; Christine Kyarimpa; Solomon Omwoma Lugasi; Thomas Rosenau; Christine Betty Nagawa; Stefan Böhmdorfer (Environmental Monitoring and Assessment, 2026)
Pyrolysis–gas chromatography–mass spectrometry (Pyr-GC-MS) has evolved into one of the most powerful methods for microplastics (MPs) analysis. However, analytical challenges are still encountered whenever Pyr-GC-MS is applied to matrices with high organic matter, protein and lipid contents. In this study, a workflow integrating stereomicroscopy, micro-Fourier transform infrared (µ-FTIR) spectroscopy and Pyr-GC-MS was extended to analyse MPs in three endemic fish species ( Protopterus aethiopicus , Rastrineobola argentea and Synodontis victoriae ) from Lake Victoria. Stereomicroscopic analysis only detected MPs in the gastrointestinal tracts of P. aethiopicus and S. victoriae , with the highest mean particle numbers being 16.0 ± 7.8 and 14.7 ± 6.7 items/fish taxon, respectively. No MPs were found in whole samples of R. argentea . The microparticles were mostly blue and brown 0.3–1.9-mm fragments and filaments, which µ-FTIR analysis confirmed to be composed of nylon 66, nylon 6/66, nylon 6/10, nylon 11, polyethylene and polypropylene. Retention time locking and post-column backflush considerably reduced the cycle time and increased stability of the Pyr-GC-MS method. Nylon 66 (243 µg/g in S. victoriae ), nylon 6 (0.24–96 µg/g), polypropylene (6.4 µg/g in P. aethiopicus ), poly(ethylene terephthalate) (1.2–107 µg/g) and styrene-butadiene rubber (8.5–34.8 µg/g) were quantified. Polyethylene and poly(methyl methacrylate) were detected below their limits of quantification. To prevent false positive detection of polyethylene in the lipid-rich tissues, the evaluation focussed on C21-α,ω-alkene as a marker. Polypropylene was not detected in some samples, as it formed several discrete propylene oligomers during pyrolysis, which suppressed the yield of its target quantification marker (2,4-dimethyl-1-heptene).

Rapid assessment of air pollution data quality using a composite index - Akhilesh Bajaj; Chad Settle (Environmental Monitoring and Assessment, 2026)

Climate-driven glacier retreat in the Sair Uul massif, Mongolian Altai (1977–2025): remote sensing, climate analysis, and field validation - Otgonbayar Demberel; Bayarmaa Munkhbat; Zolbayar Jargalsaikhan; Batsuren Dorjsuren; Battsetseg Dugersuren; Nemekhbayar Gankhuyag; Narankhuu Erdenejargal; Sainbayar Vasha; Bilegtmandakh Chuntai; Enkhsaikhan Undarmaa; Dashtseren Tsambaa; Byambanaran Hurelbaatar; et al. (Environmental Monitoring and Assessment, 2026)

Trace element accumulation in hooded crow nestlings: tissue- and age-specific patterns and implications for avian biomonitoring in riverine wetlands - Piotr Zduniak; Jakub Z. Kosicki; Izabela Komorowicz (Environmental Monitoring and Assessment, 2026)
Floodplain wetlands are dynamic ecosystems that may receive pollutants transported from upstream areas, but local exposure of wildlife to trace elements can vary depending on hydrology, bioavailability, habitat structure, and diet. In this study, we assessed the concentrations of potentially toxic non-essential elements (Cd, Pb, As) and essential elements (Cu, Se, Zn) in the blood and feathers of hooded crow ( Corvus cornix ) nestlings from a riverine wetland in Warta Mouth National Park, western Poland. Samples were collected at two developmental stages and analyzed using inductively coupled plasma mass spectrometry (ICP-MS). Concentrations of Cd, Pb, and As were consistently low in both tissues, suggesting limited exposure and/or low bioavailability of these elements in the local food web used by this omnivorous wetland-associated species. Element concentrations varied with nestling age. Older nestlings had higher blood Cu and Se concentrations. In feathers, Cd and Cu concentrations were also higher in older nestlings, whereas Zn concentrations were lower than at the earlier growth stage. These age-related differences may reflect a combination of physiological regulation, growth requirements, tissue-specific deposition, feather development, and element-specific toxicokinetics. No significant relationships were found between blood and feather concentrations, indicating that these matrices provide complementary information on exposure during nestling development. Feather Zn concentration was positively associated with nestling body condition, whereas no such relationship was detected for potentially toxic non-essential elements. Our findings highlight the importance of considering tissue type, feather ontogeny, and nestling growth stage when interpreting trace element concentrations in avian biomonitoring.

Predictive modelling of soil organic carbon, carbon stocks, and fractions across elevation gradients in the dry-temperate region of North-West Himalaya - Varun Parmar; Rushali Katoch; Naveen Datt; Pardeep Kumar; Ranbir Singh Rana; Narender Kumar Sankhyan; Rishi Mahajan; Justin George Kalambukattu (Environmental Monitoring and Assessment, 2026)

Legacy Pb–Zn mine tailings as persistent sources of bioaccessible potentially toxic elements in urban dust: geochemical signatures, exposure pathways, and human health risks - Edvaldo Renner da Costa Cardoso; Rugana Imbaná; Ésio de Castro Paes; Isabela C. F. Vasques; Oldair Vinhas Costa; Thomas Vincent Gloaguen; Emanuelle Mercês Barros Soares (Environmental Monitoring and Assessment, 2026)
Abandoned mine tailings, rich in potentially toxic elements (PTEs), can be redistributed in urban areas through atmospheric resuspension. This process serves as a dynamic geochemical compartment linking legacy contamination to human exposure. This study investigated the occurrence, oral bioaccessibility, ecological significance, and human health risks of PTEs in urban dust from Boquira, a former Pb–Zn mining district in northeastern Brazil. Eighteen urban dust samples and reference soils from uncontaminated areas were collected and analyzed for pseudo-total concentrations of Pb, Zn, Cd, Cu, Mn, Fe, and Al. Analyses were conducted using microwave-assisted acid digestion and X-ray fluorescence spectrometry (XRF). Geochemical indices, including the geoaccumulation index (I geo ), contamination factor (CF), enrichment factor (EF), and ecological risk index (Er), were used to evaluate anthropogenic enrichment and its ecological implications. Oral bioaccessibility was assessed using a simplified dilute nitric acid extraction method that simulates gastric conditions. Elevated enrichment and contamination indices revealed substantial anthropogenic inputs, particularly for Pb and Zn, indicating the long-term environmental persistence of mining-derived particulates. Pb had the highest mean oral bioaccessibility (~ 75%), followed by Cu (54.8%), Mn (28.1%), and Zn (27.0%), indicating the predominance of highly reactive and physiologically available metal-bearing phases. Human health risk assessment identified oral ingestion as the dominant exposure pathway, compared to dermal exposure, with children presenting substantially higher risks than adults. Non-carcinogenic risk thresholds (HI > 1) were exceeded for children, primarily due to Pb exposure, whereas carcinogenic risk associated with Cd ingestion exceeded acceptable limits for both population groups. The results demonstrate that legacy mine tailings in Boquira remain environmentally active decades after mine closure, sustaining chronic atmospheric redistribution of bioaccessible PTEs into urban areas.

Integrated multivariate feature selection and hydrochemical analysis for magnesium assessment in a conventional water treatment system - Ismail A. Mahmoud; Roohul Abad Khan; Musa G. Abdullahi; Surajo Sa’id (Environmental Monitoring and Assessment, 2026)

Microplastic contamination of agricultural soil in Southern India: a review and PRISMA analysis - Teena Hephzibah Nancy Inbaraj; Bahati Shabani Nzeyimana; Jefrin Luee Moses; Sharly Elgal Nirmal; Sheela Mary Mariyaselvam (Environmental Monitoring and Assessment, 2026)